AUTONOMÍA PARA APRENDER Y AUTONOMÍA PARA vivir - Narváez Ribero, Miryan (2005)
The educative system’s latest challenge is to educate independent individuals. This autonomy does not just imply that people have the necessary resources to learn to learn, but the ones they need to live together in harmony with others, listening to themselves to make their own decisions without being determined by instinctive desires nor coercive models imposed by the society. It is so, that to develop autonomy, the educational system must work with these three elements: will, freedom and self-esteem. Also, an educational system which promotes a true autonomy must have a dialogic character, insisting on the individual solidarity integration with the community; with this, we mean a person who has not resigned to his goals or aspirations, but that knows how to guide them towards a common project for the community well-being.